Use and impact of a comprehensive program of physical therapy in the treatment of patients with deforming coxarthrosis of 2-3 degrees - Borys Pustovoit; Oleksii Tets; Oksana Povìtchan; Inna Kalashnikova (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to study the effectiveness of physical therapy in the complex treatment of patients with deforming coxarthrosis of 2-3 degrees. Material & Methods: a comparative analysis of the use of traditional basic drug therapy and complex drug and physical therapy for 2 months in 30 patients (main and control group) with coxarthrosis of 2-3 degrees, functional insufficiency (FI) of 2 degrees using goniometry, visual analogue pain scale (VAS), Leiken index. Results: results of the analysis of goniometry indices, VAS and Leiken indices showed with statistical certainty the advantage of using physical therapy in the complex rehabilitation treatment of patients with coxarthrosis of 2-3 degrees, which was expressed in improving the dynamic function of the hip joint. Conclusion: a program of physical therapy for patients with coxarthrosis of grade 2-3 was developed and put into practice, including a set of ideomotor exercises, post-isometric muscle relaxation, gymnastic exercises with projectiles and objects, movement coordination exercises, breathing exercises with gravitational weights, exercises on block simulators and an exercise bike , as well as self-study at home.